Cloning and nucleotide sequence determination of the Clostridium pasteurianum ferredoxin gene. - Graves, M C (1985)
We have constructed a library of Clostridium pasteurianum DNA cloned in the plasmid pBR322. Based on the known amino acid sequence for C. pasteurianum ferredoxin, a 64-fold degenerate heptadecanucleotide pool was synthesized. This mixed probe hybridized to two clones which were shown to contain greater than 6 kilobase pairs of the same genomic DNA. Sequence analysis of a common Sau3A1 0.6-kilobase-pair fragment revealed that it contains the information for the apoferredoxin structural gene. According to the DNA sequence, the only post-translational processing of this small apoprotein is the hydrolysis of the initiator methionine. Putative transcription and translation start and stop signals are present within the sequence.